Between a demonstrative and a pronoun. The status of ’in’ in Old Swedish - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2010)
The definite article in the Modern Nordic languages is a suffix, etymologically related to a demonstrative. The form is not attested in runic inscriptions, the oldest linguistic sources, but first appears in Icelandic sagas as well as in Swedish and Danish legal codices from 13th century onwards. However, in these texts it does not appear with the same regularity as in modern languages. The Old Swedish form constitutes an intermediate form between a demonstrative, from which it is derived, and the article it has become in Modern Swedish. In the oldest texts it appears in contexts where demonstratives can only be found sporadically and its form suggests it no longer is a demonstrative. At the same time it is not yet obligatory. The aim of this paper is to show the grammaticalization of the definite article as a gradual, dynamic process, involving changes in the form and functional scope of the grammaticalizing item and to consider the properties of the Old Swedish form -in, derived from the distal demonstrative hin ‘that’.